2021
DOI: 10.3390/plants10112421
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Suppressed the Inhibitory Effects of Polyamines Inhibitors Combination in Maize (Zea mays L.) Seedlings under Chilling Stress

Abstract: Chilling stress greatly inhibited the seed germination, plant growth, development and productivity in this study. The current research aimed to study the effects of different polyamine (PA) inhibitor combinations (Co), e.g., D-arginine (D-Arg), difluoromethylormithine (DFMO), aminoguanidine (Ag) and methylglyoxyl–bis-(guanyhydrazone) (MGBG) at different doses, i.e., 10 µM Co, 100 µM Co, 500 µM Co, 1000 µM Co and 1000 µM Co + 1 mM Spd (Spermidine) in two inbred lines of maize (Zea mays L.), i.e., Mo17 and Huang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
(112 reference statements)
1
8
0
Order By: Relevance
“…Our study correlated well with these studies as 10 °C stress significantly promoted Put, Spd, and Spm accumulation (56.6–183.7%) in leaves of maize seedlings. Gao et al [ 12 ] reported that ZmADC1 , ZmADC2 , ZmODC , ZmSPDS , ZmSAMDC2 , ZmPAO1 , ZmPAO2 , and ZmPAO3 responded to biosynthesis and catabolism of PAs in maize under cold stress, which was also consistent with the expressions of GRMZM2G396553 , GRMZM2G120578 , and GRMZM2G396856 in M0504 and M1012 under 10 °C and 22 °C treatments. Thereby, these results provide a molecular basis for the utilization of PA–related genes to improve maize cold resistance in the future.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our study correlated well with these studies as 10 °C stress significantly promoted Put, Spd, and Spm accumulation (56.6–183.7%) in leaves of maize seedlings. Gao et al [ 12 ] reported that ZmADC1 , ZmADC2 , ZmODC , ZmSPDS , ZmSAMDC2 , ZmPAO1 , ZmPAO2 , and ZmPAO3 responded to biosynthesis and catabolism of PAs in maize under cold stress, which was also consistent with the expressions of GRMZM2G396553 , GRMZM2G120578 , and GRMZM2G396856 in M0504 and M1012 under 10 °C and 22 °C treatments. Thereby, these results provide a molecular basis for the utilization of PA–related genes to improve maize cold resistance in the future.…”
Section: Discussionsupporting
confidence: 64%
“…PAs are small aliphatic low–molecular weight polycationic nitrogenous compounds that played critical roles in chilling tolerance in plants [ 12 , 13 , 14 ]. Upon exposure to low temperature, the concentrations of putrescine (Put), Spd, and Spm significantly increased by 183.7%, 69.2%, and 56.6% in leaves of 39 maize genotypes seedlings, respectively ( Figure 1 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several NAC members have been practically distinguished in the developmental programs (Souer et al, 1996 ; Aida et al, 1997 ; Takada et al, 2001 ; Weir et al, 2004 ), growth hormone signaling (Xie et al, 2000 ; Fujita et al, 2004 ), defense (Collinge and Boller, 2001 ; Hegedus et al, 2003 ), and leaf senescence (Fraga et al, 2021 ). Various NAC genes participate in reactions to abiotic stresses, which include flood, water deficit, salinity, and cold (Fujita et al, 2004 ; Olsen et al, 2005 ; Hu et al, 2006 ; He et al, 2017 ; Gao et al, 2020 , 2021 ; Mao et al, 2021 ). Enhanced expression of ZmNAC48 was detected in maize plants subjected to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%